2014
DOI: 10.1159/000362638
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neurogenesis: A Promising Therapeutic Strategy for Post-Stroke Treatment with Chinese Herbal Medicine

Abstract: Recent progress suggests that neural stem/progenitor cells can potentially develop into new functional neurons in adult brain, offering hope for regeneration therapies for stroke treatment. Targeting adult neurogenesis becomes a novel and promising therapeutic strategy for brain repair and recovery of neurological functions. Traditional Chinese Medicine (TCM) has a long history with accumulated experiences and case reports using herbal formulas to treat stroke disability. The combination of Chinese herbal medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Chinese medicine has the distinctive function of modulating the body or dealing with diseases, including treating brain problems [ 31 , 32 ]. We are still unable to show how the ingredients pass through the blood-brain barrier (BBB), but they have been used in many countries for treating many diseases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicine has the distinctive function of modulating the body or dealing with diseases, including treating brain problems [ 31 , 32 ]. We are still unable to show how the ingredients pass through the blood-brain barrier (BBB), but they have been used in many countries for treating many diseases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study found that Nao-Xue-Shu oral liquid has a markedly lower incidence of SBI, inhibits the accumulation of hematoma, improves the absorbance of hemorrhage, eliminates the toxic stimulation of peripheral brain tissue, and inhibits the accumulation of inflammatory factors [28]. Chinese medicine has the distinctive function of modulating the body or dealing with diseases, including the treatment of brain problems [29,30]. We are still unable to show how the ingredients pass through the blood-brain barrier, but they have been used in many countries for treating many diseases [31].…”
Section: Discussionmentioning
confidence: 99%
“…In TCM theory, each Chinese medicine has its own function to modulate the body or deal with diseases, including treating brain problems, but doctors in China are still unable to demonstrate how the medicine passes through the blood brain barrier (BBB). Including TCM herbs [ 26 , 27 ], many integrative medicines such as Ayurveda medicine [ 28 ], electric stimulation [ 29 ], and Tai Chi quan [ 30 ] cannot confirm that they influence the nerve system directly by Western medical technology, but they have been used in many countries for treating many diseases [ 5 ]. Nao-Xue-Shu oral liquid contains a type of worm and this is another problem since, according to ethics, it is difficult to introduce such a treatment into foreign countries, although worms are frequently used in TCM treatments and TCM researchers in China have demonstrated they are harmless and safe.…”
Section: Discussionmentioning
confidence: 99%